ANALISIS PERBANDINGAN KEPUASAN NASABAH PADA SISTEM ANTRIAN TELLER BANK, MENGGUNAKAN NOMOR DAN TANPA NOMOR STUDI PADA BANK BNI CABANG MOROTAI - Wangko, Lukman (Jurnal Pendidikan dan Ekonomi (JUPEK), 2023)
This study is intended to compare the two queuing systems, in order to obtain information regarding the highest level of customer satisfaction. The research method used is a comparative descriptive survey research method, which aims to compare and provide an overview of existing facts. The queuing system variables studied are arrivals, queues, and services. Data from 100 questionnaires distributed randomly (simple random sampling) to customers of Bank BNI Morotai Branch became the primary data source. Based on the analysis of the level of customer expectations compared to the actual performance of the queuing system, it can be concluded that there is an increase in customer satisfaction after the replacement of the queuing system, which was initially a queuing system without numbers to a queuing system using numbers. indicates that there is a significant difference between the average level of performance of the queuing system using numbers and the queuing system without numbers. By using comparative analysis, it is known that customers have a higher level of satisfaction in the queuing system using numbers.